Формирование и свойства биоактивных покрытий на титане; Перспективные материалы; № 2 - Гнеденков С. В. Сергей Васильевич; Шаркеев Ю. П. Юрий Петрович; Синебрюхов С. Л. Сергей Леонидович; Хрисанфова О. А. Ольга Алексеевна; Легостаева Е. В. Елена Викторовна; Завидная А. Г. Александра Григорьевна; Пузь А. В. Артем Викторович; Хлусов И. А. Игорь Альбертович (2011, 2011)
Заглавие с экрана